2023
DOI: 10.1007/s11465-023-0752-4
|View full text |Cite
|
Sign up to set email alerts
|

Equipment-process-strategy integration for sustainable machining: a review

Lianguo Wang,
Wei Cai,
Yan He
et al.

Abstract: Although the manufacturing industry has improved the quality of processing, optimization and upgrading must be performed to meet the requirements of global sustainable development. Sustainable production is considered to be a favorable strategy for achieving machining upgrades characterized by high quality, high efficiency, energy savings, and emission reduction. Sustainable production has aroused widespread interest, but only a few scholars have studied the sustainability of machining from multiple dimensions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 203 publications
0
1
0
1
Order By: Relevance
“…Existen diversas técnicas y enfoques para operaciones de mecanizado sostenibles, dado que, muchos investigadores han encontrado reemplazos, beneficiando la salud de los trabajadores, minimizando los costos de mecanizado y reduciendo el impacto en el medio ambiente, entre los principales se destacan (Wang et al, (2023)  Mecanizado en Seco: La ausencia de fluidos de corte en el mecanizado se denomina mecanizado en seco, ganando prominencia en el mundo manufacturero por su amabilidad ambiental, satisfacción del trabajador, disminución del costo de refrigerante y reducción del flujo de fugas. Un experimento realizado en hierro grafito compactado para 3150 agujeros mediante el proceso de taladrado ha demostrado la viabilidad del mecanizado en seco, aunque presenta desafíos como dimensiones imprecisas de la pieza de trabajo y reducción en la vida útil de la herramienta debido a altas temperaturas en el área de mecanizado.…”
Section: Resultsunclassified
“…Existen diversas técnicas y enfoques para operaciones de mecanizado sostenibles, dado que, muchos investigadores han encontrado reemplazos, beneficiando la salud de los trabajadores, minimizando los costos de mecanizado y reduciendo el impacto en el medio ambiente, entre los principales se destacan (Wang et al, (2023)  Mecanizado en Seco: La ausencia de fluidos de corte en el mecanizado se denomina mecanizado en seco, ganando prominencia en el mundo manufacturero por su amabilidad ambiental, satisfacción del trabajador, disminución del costo de refrigerante y reducción del flujo de fugas. Un experimento realizado en hierro grafito compactado para 3150 agujeros mediante el proceso de taladrado ha demostrado la viabilidad del mecanizado en seco, aunque presenta desafíos como dimensiones imprecisas de la pieza de trabajo y reducción en la vida útil de la herramienta debido a altas temperaturas en el área de mecanizado.…”
Section: Resultsunclassified
“…In addition, it has been shown that a method called low-temperature plasma can effectively adjust material properties, including hardness, strength, ductility, and wettability, significantly improving material machinability. Liu's group [5] discussed the mechanisms and applications of low-temperature plasma-assisted machining as well as described the effects of the lowtemperature plasma on different machining processes of various difficult-to-cut materials. They found that hot plasma improved material machinability via the thermal softening effect induced by the high temperature, whereas the main mechanisms of the cold plasma can be summarized as chemical reactions to reduce material hardness, the hydrophilization effect to improve surface wettability, and the Rehbinder effect to promote fracture.…”
mentioning
confidence: 99%